(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In this article, the semantic relations between words within the framework of Uzbek linguistics, including nesting, are discussed in detail. Also, scientific-theoretical views about similar and different aspects of nesting with other lexical-semantic types are stated.